Nicholas Nickleby Level 4 - Dickens, Charles; Rice, Chris; Hopkins, Andy; Potter, Jocelyn (England Pearson Education Ltd, 2007)
Nicholas Nickleby is a novel about a young man who must support his family after his father's death. He works at a cruel boarding school but eventually escapes and tries various jobs. Along the way, Nicholas defends the helpless, confronts corrupt relatives, and fights for justice. With courage and kindness, he overcomes hardships and finds happiness for himself and his loved ones.
Keywords: Tham khảo